Analysis Of Determinant Factors Of Purchase Decisions For Garnier Facial Wash Products (Study On The General Public In Tegal City) - Evan Fauzan Putra; Erny Rachmawati; Sri Wahyuni; Wida Purwidianti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Garnier was one of the alternative choices for facial wash products that were in high demand by the public. Garnier Facial Wash became a daily necessity for facial care for both men and women. The purpose of this study was to examine the influence of celebrity endorsers, brand image, brand trust, lifestyle, and product quality on purchasing decisions for Garnier Facial Wash products. The target population of this study was the general public in Tegal City with range age 17-30 years , good man and also women who have ever do purchase and use Garnier Facial Wash products. This study employed a quantitative method using purposive sampling, resulting in data from 115 respondents, which were analyzed using a five-point Likert scale. The data were processed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The findings of this study indicated that celebrity endorsers, brand image, brand trust, and product quality had a positive effect on purchasing decisions, whereas lifestyle did not have a significant impact.